Sensory Test of Chia Seed in Yoghurt with Ginger (Zingiber Officinale R) as Natural Preservative - Asyraf Huda; Nurmahni Harahap (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
Yoghurt is a milk-processed product that is fermented using Bacillus bulgaricus and Bacterium thermophilus. The method of preparation is based on centuries of experience in placing naturally contaminated milk at high temperatures of about 40–50 °C. Yoghurt is a healthy drink made from fermented milk. The aim of this study was to identify and test the influence of adding chia seeds to fermented milk on physical or sensory properties such as texture, aroma, taste, and panel preference. This method of research is experimental. Researchers conduct experimental research to explore the consequences of their deliberate actions. The results of the analysis of milk (yoghurt) are the colour of the lk (yogurt), wh which has a percentage of SS=40% and S=40%, while TS=20%. Aroma in milk that has a percent of sebum is SS=30%, S=70%, and TS=0%. Texture in milks that have a percent sebum of S = 80%, S = 20%, and TS = 0%).